On the R-automorphisms of formal power series on several indeterminates and with coefficients over the ring R - Soledad Ramírez C.; Anderson Cárdenas F. (Selecciones Matemáticas, 2022)
In this paper, we show a way to characterize the R-automorphisms of formal power series on several indeterminates and with coefficients over a commutative ring with identity, R. We show this characterization, as an extension of existing result for the R-automorphisms of the formal power series in an indeterminate, given by O’Malley, M. and Wood, C. in [12].